Lesson Study and the development of teacher’s competences. From practical knowledge to practical thinking - Soto-Gómez, Encarnación; Servan-Núñez, María José; Pérez-Gómez, Ángel Ignacio; Peña-Trapero, Noemí (Emerald, 2015)
Purpose – The purpose of this paper is to show, from a theoretical point of view, the promising relationship between the processes generated by Lesson Studies (LS) and the development of practical thinking in in-service teacher training, derived from two pieces of research. Design/methodology/approach – The authors propose broadening the focus of LS in order to not only improve the “lesson” or “teaching” – in short, practice – but also to reconstruct and improve the practical knowledge of teachers. The core issue of the paper is the discussion about the relationship between the practical knowledge, the knowledge that every teacher uses in his or her daily practice, theories-in-use, mostly unconscious, and the conscious and explicit knowledge, practical thinking, explicit theory, they use to describe and justify their practice. Findings – Knowing our practical knowledge intuitive Gestalt, and building a new conscious and informed way of thinking is not enough, we need to build through systematic new practice a new way of doing, a new way of perceiving, interpreting, taking decisions and acting, coherent with our new theories. LS reinforces these two complementary movements: the practical theorizing movement, the reflexion on action to discover the implicit believes, habits, attitudes and emotions underlying the practice, and the experimentation of the new theory to form the new habits, beliefs, attitudes and emotions that support the development of a new form of teaching. This second movement needs more time and adequate teaching context, confirming the long spiral cycle of LS. Originality/value – With emphasis on the dialectical relationship between practical theorizing and the experimentation of theory, this paper could set out a new approach for LSs as a method of teacher training which can improve practice through the reconstruction of the practical thinking of those involved.
Keywords: Profesores - Formación profesional; Teacher training; Lesson study; Practical knowledge; Practical thinking; Reconstruction; Theories in use